Pedestrian Way Assets Performance Analysis Based on Pedestrian Level of Service (PLOS) In Lembang Street Segment - Tiafahmi Angestiwi; Sabila Masturah (Universitas Islam Sultan Agung Semarang, 2026)
The pedestrian ways on Jalan Lembang is a public asset that plays a vital role in supporting public mobility. However, there are indications of problems affecting its function. The purpose of this study is to analyze the performance of the pedestrian ways based on six aspects of the Pedestrian Level of Service (PLOS) assessment. The research method used is descriptive research with a quantitative approach. Data collection techniques include direct observation and questionnaires distributed to sidewalk users. The results of the study indicate a low level of safety due to the lack of separation between pedestrians and vehicle traffic with a very poor level of service. The infrastructure and security aspects of sidewalk lighting are considered inadequate with a very poor level of service due to the potential for crime. The comfort and safety aspects are still considered very poor due to the presence of street vendors and shelters that are not friendly to the elderly and disabled users. The final aspect is violations on the sidewalk with a very low level of service due to the presence of informal businesses and semi-permanent buildings along the sidewalk. Based on the explanation of the six aspects of PLOS service, it can be concluded that the pedestrian ways on Jalan Lembang is at level E, meaning it does not meet the minimum standards of decent service.Keywords: Asset Performance Analysis, Pedestrian Ways, Pedestrian Level of Service, Public Assets Jalur pejalan kaki di Ruas Jalan Lembang merupakan bagian dari aset publik yang memiliki peran penting dalam mendukung mobilitas masyarakat. Namun demikian, terdapat indikasi permasalahan yang memengaruhi fungsinya. Tujuan penelitian ini adalah untuk menganalisis kinerja jalur pejalan kaki berdasarkan enam aspek penilaian Pedestrian Level of Service (PLOS). Metode penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kuantitatif. Teknik pengumpulan data meliputi observasi langsung dan penyebaran kuesioner kepada pengguna trotoar. Hasil penelitian yang dilakukan yakni, menunjukkan tingkat keselamatan yang rendah dikarenakan tidak adanya pemisah antara pejalan kaki dengan lalu lintas kendaraan dengan tingkat pelayanan sangat buruk. Aspek infrastruktur dan keamanan penerangan trotoar dinilai belum memadai dengan tingkat pelayanan sangat buruk karena terdapat potensi tindak kriminal. Aspek kenyamanan dan keamanan dinilai masih sangat buruk dikarenakan masih terdapat pedagang kaki lima dan tempat berteduh yang tidak ramah lansia dan pengguna disabilitas. Aspek terakhir berupa pelanggaran terhadap trotoar dengan tingkat pelayanan sangat rendah karena masih terdapat usaha informal dan bangunan semi permanen di sepanjang trotoar. Berdasarkan pemaparan keenam aspek pembentuk pelayanan PLOS, dapat disimpulkan bahwa jalur pejalan kaki di Ruas Jalan Lembang berada pada level E, artinya belum memenuhi standar minimum pelayanan yang layak.Kata kunci: Analisis Kinerja Aset, Aset Publik, Jalur Pejalan Kaki, Pedestrian Level of Service, Prasarana Jalan